2023
DOI: 10.14421/biomedich.2023.121.127-132
|View full text |Cite
|
Sign up to set email alerts
|

In-Vivo Alpha-Amylase and Alpha-Glucosidase Inhibitory Activities of Solanum anomalum Leaf Extract and Fractions

Abstract: Solanum anomalum Thonn. ex Schumach. (family Solanaceae), an edible shrub whose fruits and leaves are used medicinally to treat diseases including diabetes was evaluated for effect on alpha amylase and alpha glucosidase enzymes in vivo. The leaf extract (70-210 mg/kg) and fractions (hexane, dichloromethane, ethyl acetate, methanol, 140 mg/kg) of S. anomalum were evaluated in vivo for inhibitory effect on alpha amylase and alpha glucosidase enzymes using starch, sucrose and maltose as substrates. Acarbose was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This effect could be due to the free radicals scavenging potentials of the root extract/fractions and its antioxidative stress activity [6,11]. These activities can be linked to the phytochemical constituents of the root extract, such as monoterpenes, sesquiterpenes, and xanthones, which have previously been reported to be present [6,11,14].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This effect could be due to the free radicals scavenging potentials of the root extract/fractions and its antioxidative stress activity [6,11]. These activities can be linked to the phytochemical constituents of the root extract, such as monoterpenes, sesquiterpenes, and xanthones, which have previously been reported to be present [6,11,14].…”
Section: Resultsmentioning
confidence: 95%
“…For the treatment of liver conditions including hepatitis and jaundice, the plant's root is also used for its antidote or antipoison properties [3][4][5]. It has been reported that the root extract has antimalarial [2,6], antioedema and antinociceptive [7], antidiabetic and hypolipidemic [8,9], antidiarrhoeal and antiulcer [10], hepatoprotective [11], antileishmanial, cytotoxicity and cellular antioxidant [12], antibacterial, anticonvulsant and depressant [13], in vivo alpha amylase and alpha glucosidase inhibitory [6], in vitro antioxidant [9,14] activities. Previous research has indicated that the ethyl acetate fraction contains spirohexane-1-carboxylic acid, ethyl ester, 3methoxy-2-methylphenol, 2,3-benzofurandione, 6-hydroxy-4-(p-hydroxybenzyl), თ-3-Carene, and α-terpineol [15] and the n-hexane fraction of the root exract contains monoterpenes (limonene, thujene, linalool, α-phellandrene, α-terpineol, and sabinene) and sesquiterpenes (dehydromevalonic lactone).…”
Section: Introductionmentioning
confidence: 99%
“…The ripe eggplant fruits are usually discarded partly due to their low acceptability and the ignorance of their benefits and thus are among the post-harvest food crops lost after harvest in Nigeria, West Africa. Meanwhile, a study [10] showed that ripening brings changes in the fruit content of phenolic compounds, organic acids, and carbohydrates, as well as in its color, texture, and flavor [10].…”
Section: Introductionmentioning
confidence: 99%
“…"The plant's root is also use for its antidote or antipoison potential to treat liver diseases such as jaundice and hepatitis" [3,4,5]. Previous reports showed that the root extract possess antimalarial [2,6], antioedema and antinociceptive [7], antidiabetic and hypolipidemic [8,9], antidiarrhoeal and antiulcer [10], hepatoprotective [11], antileishmanial, cytotoxicity and cellular antioxidant [12], antibacterial, anticonvulsant and depressant [13], in vivo alpha-amylase and alpha-glucosidase inhibitory [6], in vitro antioxidant [6,9] activities. Earlier studies had reported the presence of spirohexane-1-carboxylic acid, ethyl ester, 3-methoxy-2-methylphenol,2,3benzofurandione,6-hydroxy-4-(p-hydroxybenzyl), ᵟ-3-Carene and α-terpineol in ethyl acetate fraction [14] and the presence of monoterpenes (thujene, limonene, linalool, αphellandrene, α-terpineol and sabinene) and sesquiterpenes (dehydromevalonic lactone), in the n-hexane fraction of the root extract [11].…”
Section: Introductionmentioning
confidence: 99%